Crystallization of 3-hexulose-6-phosphate synthase - Delfi, Masoud; Mahdavian, Leila; Sattarifar, Mohammad; Hakulinen, Nina; Rouvinen, Juha (European Journal of Chemistry, 2021)
The crystal structures can reveal detailed information about the overall structure, active site structure, and functional mechanism of enzymes. This study focused on the crystallization of 3-hexulose-6-phosphate synthase from Methylomonas aminofaciens 77a, to produce higher resolution crystals for precise structural characterization. 3-Hexulose-6-phosphate synthase is from Methylomonas aminofaciens 77a (EC 4.1.2.43). It belongs to the orotidine 5’-monophosphate decarboxylase superfamily, and acts as a key enzyme for a ribulose-monophosphate cycle of formaldehyde fixation and detoxification. 3-Hexulose-6-phosphate synthase catalyzes the aldol condensation of formaldehyde with D-ribulose-5-phosphate. For the maximum activity, 3-hexulose-6-phosphate synthase requires Mg2+ or Mn2+ as ligands. MaHPS crystallized at the concentration of 7 mg/mL and conditions consisting of 0.2 M MgCl2, 18% PEG 3350 at pH = 7.0.